Pengembangan Lembar Kerja Peserta Didik Berbasis Budaya Lokal pada Materi Kekayaan Budaya Indonesia - Syahra, Neneng; Munawir, Ahmad; K, Nurdin (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article discusses research on the development of Local Culture-Based Learner Worksheets on Indonesian Cultural Wealth Material for Class IV SDN 468 Bilante, Larompong District, Luwu Regency. This study aims to analyze the needs of Local Culture-Based Learner Worksheets (LKPD) on Indonesian Cultural Wealth Material. This type of research is research and development (R&D) with the ADDIE development model. This research was conducted in 2024 involving 18 fourth grade students of SDN 468 Bilante, while the object of research was the Learner Worksheet (LKPD) developed according to the needs of students. The research data were collected through questionnaires, interviews, and tests then analyzed qualitatively and quantitatively. Based on the results of the study, the use of LKPD in increasing the knowledge of students, based on the results of the validity of the Learner Worksheet (LKPD) with categories including linguists getting a percentage worth 85% with a very valid category, material experts get a presentation value of 92% with a very valid category, while design experts get a percentage value of 81% with a very valid category. Based on the results of the practicality lift, a presentation of 86% for students and 89.5% for educators was obtained. Then the effectiveness of LKPD users with a presentation of 92% is very valid category. Based on the results of the study, the use of LKPD in increasing students' knowledge, based on the needs analysis that has been carried out in class IV SDN 468 Bilante, shows that the product that has been successfully developed is a local culture-based LKPD on the material of Indonesia's cultural wealth in class IV and this LKPD has been adjusted to the needs of students.